2018
DOI: 10.1007/s12026-018-8988-5
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and oxycytosis: two arms of human innate immunity

Abstract: Human innate immunity operates in two compartments: extravascular (the tissues) and intravascular (the bloodstream). Physical conditions (fluid dynamics) in the compartments are different and, as a result, bactericidal mechanisms and involved cells are different as well. In relatively static media (the tissues, lymph nodes), bacteria are killed by phagocytes; in dynamic media (the bloodstream), bacteria are killed by erythrocytes. In the tissues and lymph nodes, resident macrophages and transmigrated from bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 91 publications
0
41
0
Order By: Relevance
“…Because HlyA certainly has the potential to change the behaviour or even lyse circulating immune active cells like monocytes (Fagerberg, Jakobsen, Skals, & Praetorius, ), the presence of HlyA could potentially interfere with intravascular bacterial clearance. Interestingly, the intravascular clearing of bacteria mechanistically has recently been argued to be markedly different from more solid tissues (for a review, see Minasyan, ). This review extracted documentation for the collective phagocytic system being too slow and having too low a capacity to effectively clear bacteria from the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because HlyA certainly has the potential to change the behaviour or even lyse circulating immune active cells like monocytes (Fagerberg, Jakobsen, Skals, & Praetorius, ), the presence of HlyA could potentially interfere with intravascular bacterial clearance. Interestingly, the intravascular clearing of bacteria mechanistically has recently been argued to be markedly different from more solid tissues (for a review, see Minasyan, ). This review extracted documentation for the collective phagocytic system being too slow and having too low a capacity to effectively clear bacteria from the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the author argues for the erythrocyte as the main cell involved in intravascular bacterial clearance. The triboelectric charge of erythrocytes is mainly responsible for attracting and adhering of bacteria to erythrocytes, which are then able to kill the bacteria via its high oxygen content and release of reactive oxygen species (Minasyan, ). The ζ‐potential of the erythrocytes is mainly caused by sialic acid and can be markedly reduced by neuraminidase treatment (Munksgaard et al, ), but the ability of bacteria to adhere also depends on density, elasticity, and shape (Minasyan, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocytes play an important role in human innate immunity. Bacteria in the bloodstream can be attracted and kept by erythrocytes and killed by oxidation [23,24]. There is no doubt that erythrocytopenia would undermine the protective mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being crucial for pathogen recognition through the mammalian cysteine protease caspase-1, a central enzyme of innate immunity, which processes pro-interleukin-1 (IL-1)β into the mature proinflammatory cytokine IL-1β, the discovery of monogenic and polygenic disorders in which inflammasome activity and IL-1 release are deregulated highlights the essential importance of inflammasome-supervised human defences against infections. 1 Different studies have demonstrated the existence of a functional hierarchy of proinflammatory cytokines in systemic autoinflammatory disorders (SAIDs), a heterogeneous cluster of rare genetically determined diseases involving innate immunity, mainly characterized by the recurrence of inflammatory flares affecting the skin, joints, serosal membranes, gastroenteric tube, central nervous system and other tissues, in which IL-1β is the most critical driver of inflammation at different levels. 2 , 3 The term “autoinflammatory” describes the nearly spontaneous appearance of inflammation in the almost complete absence of autoreactive T lymphocytes and/or specific autoantibodies and no clear evidence of infectious triggers.…”
Section: Introductionmentioning
confidence: 99%